Haunted is always in fashion - Pressey, Rose (Pressey, Rose. Haunted vintage mystery., 2016)
"As the owner of It's Vintage, Y'all in Sugar Creek, Georgia, Cookie Chanel has agreed to share her expertise with author Juliana McDaniel. But on her way to town, Juliana is hot dead, and that was all she wrote. Cookie picks up the thread of the story with help from her psychic cat and a couple of inquisitive ghosts. To unmask this killer, she'll have to lift the lid on family secrets and hidden motives- because she might wind up getting capped herself if she doesn't cloche this case..."